Chapter Population ageing and sustainability in South Tyrol: measuring the economic implications of an ageing society - Cavrini, Giulia (Proceedings e report, 2023)
Meeting the challenge of population ageing requires a better understanding of frailty and disability, and appropriate strategies to ensure the resilience of the health and social care system, without destabilising public finances or over-burdening the economy. An increasing life expectancy will primarily affect the health care and the long-term care spending. Countries will face an ongoing challenge to provide care for a heterogeneous population of older adults. Within this context, the current paper is designed to (a) measure the current needs for social care in South Tyrol, (b) identify the local trajectories of health status, disaggregated by age, sex and severity of illness, (c) forecast the health care needs and the healthcare system's financial sustainability. Demographic forecast data (up to 2050) on population age and sex structure is provided by ISTAT . Health care data for administrative and billing purposes is from the Autonomous Province of Bozen-Bolzano, which are used to study health care delivery, benefits, harms, and costs. Preliminary results show a decrease in the prevalence of individuals receiving home care allowance from 2009 to 2019 for all levels of severity and both for men and women. Overall, greater prevalence occurs at lower levels of health condition severity (levels 1 and 2 over a four points-scale of severity) and after age 75. Historical payments combined with the demographic forecast allow for an estimate of yearly average costs individual recipients (by age, sex, and health condition) as well as for the whole local social system.